Analisis Makna Simbolik Ornamen Kuil Buddha Dalam Konteks Keagamaan: Studi Kasus Maha Vihara Maitreya - Utari, Diah Sri; Arifinsyah, Arifinsyah; Ekowati, Endang (Jayapangus Press, 2024)
The aim of this research is to understand and analyse the symbolic meaning of the ornaments in the Mahabharata Maitreya Temple as well as the role of these ornements in conveying the teachings and values of Buddhism. Maha Vihara Maitreya is located in the city of Medan, Indonesia. It is one of the largest Buddhist temples in Indonesia and has a variety of architectural and decorative elements that are rich in symbolic significance. Maha Vihara Maitreya also adopted many of the characteristic elements of China in every detail of the building and its ornaments. The research uses a qualitative approach with case study methods that include field observations, in-depth interviews with one of Vihara's managers and related literature analysis. The results showed that every element in the Majesty Maitreya, from the architecture of the building to the ornaments on the sculpture, had a profound symbolic significance and served as a medium for the transmission of Buddhist teachings to its followers. In addition, the temple also played an important role in strengthening the Buddhist identity of the field and its surroundings, as well as becoming a centre of religious and cultural activity. This research has made important contributions to the understanding of symbolism in Buddhist religious architecture and its implications for religious practice and identity of communities, in the city of Medan, North Sumatra.